Is age associated with emergency medical service transport to a trauma centre in patients with major trauma? A systematic review - Brown, E.; Tohira, Hideo; Bailey, P.; Finn, Judith (2020)
© 2020, Paramedics Australasia. All rights reserved. Introduction Older adults with major trauma are known to have higher mortality rates than their younger counterparts and there is a known survival benefit of treatment in trauma centres. This systematic review sought to answer the question: are older patients with major trauma more or less likely to be transported to a trauma centre by emergency medical services (EMS) than younger patients? Methods The following databases were searched: Ovid MEDLINE, Ovid EMBASE, EBSCO CINAHL, Scopus, Cochrane Library and grey literature until 7 March 2019. Studies meeting each of the following criteria were included: 1) comparative study, including randomised controlled trials, cohort studies, cross-sectional studies, case-control studies; 2) study participants must be patients with major trauma; 3) the patients must have been initially transported from the accident scene to hospital by EMS, and 4) the study must report the association between major trauma patient, age and trauma centre transport. Results We identified 3365 unique citations and one study was identified through other sources. In total, 17 studies were included. The studies defined major trauma patients either by the meeting of pre-hospital trauma triage criteria or a retrospective diagnosis. All of the included studies reported that older age was associated with a reduced likelihood of EMS trauma centre transport when compared to younger age in major trauma patients. Conclusion The studies included in this review all showed that older age is associated with a reduced likelihood of EMS trauma centre transport when compared to younger age in major trauma patients.